Canagliflozin: A Comprehensive Review of Advances in Preclinical Research - Imran, Bushra; Ahsan, Farogh; Mahmood, Tarique; Khan, Mohd Masih Uzzaman; Bano, Shahzadi; Zaidi, Syed Mehdi Hasan; Ansari, Jamal Akhtar; Singh, Aditya (Drug Research, 2025)
Canagliflozin is a synthetic sodium glucose transporter inhibitor (SGLT2i). It is the latest approved class of medicine used in the treatment of type 2 diabetes mellitus. As diabetes is emerging as the most common metabolic disorder, SGLT2i has lightened up the path of treatment with additional benefits. SGLT2 is located in the proximal convoluted tubules of the nephron and is responsible for glucose reabsorption. Thus, inhibiting the SGLT2 leads to a decline in glucose concentration in the plasma. The secondary effects of canagliflozin, such as cardiac protection, renoprotective, and decreased obesity, have made it more putative in the treatment of diabetes mellitus. There are some side effects of canagliflozin, such as volume depletion, genital and urinary tract infection, and lower limb amputation, which could be a matter of concern for patients. Being an anti-diabetic drug, canagliflozin also possesses anti-inflammatory and anti-cancer properties. Several studies have been conducted to determine the efficacy of canagliflozin as an anti-cancer agent. Its pharmacokinetics indicate rapid absorption, reaching peak plasma concentrations within 1–2 hours. With a half-life of approximately 12 hours, it undergoes minimal hepatic metabolism and is primarily excreted unchanged via urine. Common adverse drug reactions (ADRs) include urinary tract infections and dehydration. Clinical trials on canagliflozin, both alone and in combination with other diabetes complications, have been conducted, with some completed and others in various phases. This review article contains information about the pharmacokinetics, drug safety, and efficacy profile of canagliflozin, along with details regarding toxicological studies of canagliflozin.
Keywords: canagliflozin; SGLT-2 inhibitors; sodium-glucose transporter; obesity; drug safety; heart failure